Red to near-infrared piezochromism from AIE-active luminophores: isolated dimers facilitating a wide-range redshift. (6th April 2022) - Lv, Long; Ye, Lijie; Cao, Feng; Yang, Shengchen; Song, Qingbao; Zou, Bo; Wang, Kai; Lv, Chunyan; Zhang, Cheng; Zhang, Yujian
Abstract : An AIE-activity architecture with HLCT and highly bright fluorescence was developed and it was the dispersed dimer packing found to be attributable to cholesteryl units. During compression, the dispersed dimers presented a remarkable redshift (157 nm) and high sensitivity (22.1 nm GPa −1 ). Abstract : Near-infrared piezochromic materials (PCMs), presenting a fluorescence response with a clear colour difference (large spectral shift) and strong penetrability, have practical applications as pressure sensors. Nevertheless, examples achieving a distinct redshift are very rare in the deep-red to near-infrared region. Herein, an asymmetric luminophore, TDCH, was developed by end-capping a benzothiadiazole core with nonconjugated cholesteryl and twisty triphenylamine (TPA) units, which exhibits aggregation-enhanced emission behaviour. Impressively, TDCH molecules adopt isolated dimeric packing and emit deep-red fluorescence at 675 nm with a high emission efficiency (89.7 and 44.3% for doped film and crystalline powder, respectively). These neighbouring dimers, fully separated by TPA units, are related to the nonconjugated cholesteryl groups. At high pressure, π–π interactions between adjacent dimers are weakened by nonconjugated cholesteryls. As a result, this luminophore demonstrates the deep-red to near-infrared piezochromic properties with a wide-range redshift (157 nm) and high sensitivity (22.1 nm GPa −1 ).